P144 Staff engagement survey pre- and 6-months post introduction of routine domestic abuse enquiry. (30th June 2016) - Sacks, Rachel; Ponnusamy, Nora; Mears, Alison
Abstract : Background/introduction: In July 2015, routine domestic abuse (DA) enquiry was introduced in a busy, walk-in, inner-London, genitourinary medicine (GUM) clinic. Guidelines, proforma and management pathway were devised. Tiered training was/is provided (basic level for all staff, in-depth for Sexual Health Information Protection team and DA champions). A separate audit demonstrated 91% of walk-in GUM patients were asked about DA, following routine enquiry introduction. Aim(s)/objectives: To assess staff engagement with routine DA enquiry. Methods: On-line survey disseminated to GUM healthcare professionals, two weeks prior to, and 6 months post-introduction of, routine DA enquiry. Results: 27 vs 20 staff completed the surveys. The majority were female [70 vs 90%]. Respondents were doctors [48.1% vs 42.1%], nurses [44.4% vs 57.9%] and healthcare assistants [7.4% vs 0%]. 3.7% vs 20% had worked in GUM < 1 year. 87.5% vs 89.5% had received training, 85.0% vs 100% of these respectively had rated this good-excellent. 4.8% vs 66.7% of respondents reported having managed patients disclosing DA at least once/week. 14.3% pre-introduction vs 0% post-introduction respondents had never managed a patient disclosing DA. Respondents reported feeling 'very confident' asking about DA [16.7% vs 63.2%] and managing disclosures [8.3% vs 26.3%]. 45.8% vs 63.2% thought 'Routine DA enquiry was a great idea…why hadn't we introduced earlier?' 8.3% pre-introduction respondents had some reservations vs 0% post-introduction. Discussion/conclusion: Staff engagement in routine DA enquiry was high from the outset and improved over 6 months. Levels of experience and confidence in DA enquiry and disclosure management improved dramatically over this period.